Reframing Ethic and Spirit: The Key of Successful of Educational Leadership - Aroum Bidandari, Amin Fauzi, Riana Fathonatul Qoidah, Fatimah Gloria da C., Muhammad Sholeh (Lembaga Bale Literasi, 2025)
In the modern digital era, educational leadership faces a moral and spiritual crisis that affects the quality of education and public trust. This study addresses the problem by examining how ethics and spirituality contribute to the effectiveness and integrity of educational leadership. The research aims to analyze the relevance of ethical and spiritual values in shaping successful leaders and to identify the challenges in implementing these principles in current educational contexts. Using the Systematic Literature Review (SLR) method, this study collected and analyzed data from relevant books and academic journals. The results reveal that ethical and spiritual foundations are essential in guiding leaders to act wisely, make just decisions, and build trust within educational institutions. The study concludes that integrating ethics and spirituality enhances leadership effectiveness, fosters moral awareness, and strengthens organizational harmony ultimately supporting the realization of a shared educational vision.